Penyelesaian Sengketa Pinjaman Online Melalui Mediasi - Aswan Aswan (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2024)
The rapid development of information technology has significantly transformed the financial sector, particularly with the rise of online lending services or fintech lending. While these services provide easier access to financial resources, they also bring various challenges, including an increase in disputes between lenders and borrowers. The government, through the Financial Services Authority (OJK), has formulated regulations to protect consumers and promote the use of mediation as an alternative dispute resolution method that is more efficient and less burdensome for both parties. This study aims to analyze the effectiveness of mediation as a solution for resolving online lending disputes, using a normative juridical approach. Data were collected from various primary and secondary legal sources and analyzed deductively. The results indicate that mediation offers a faster, more flexible, and less formal mechanism compared to court proceedings. However, challenges such as low consumer financial literacy and a lack of understanding by service providers about the mediation process need to be addressed through increased education and awareness campaigns. In conclusion, mediation has great potential to become a more equitable and efficient dispute resolution mechanism in the fintech lending industry, provided it is supported by adequate regulations and improved awareness among the involved parties.